Two Morphologically Different Strains of Himalayan Alder (Alnus nepalensis D. Don.) Trees from Same Seedlot - Kediyal, Vijyendar Kumar; Bijalwan, Arvind; Singh, A.K. (Indian Journal of Agroforestry, 2020)
Himalayan alder (Alnus nepalensis DDon.) is one of the fast growing multipurpose tree species for climatically cooler regions. Usually the trees from same seed source are felt genetically similar. This species is felt as one of the most suitable for water spring rejuvenation. Seedlings are raised through seeds. Broadly every seedling grows morphologically with very little variations. Two morphologically different strains were transplanted on homogeneously similar location and different observations were collected at the age of three years. These two strains are found distinct from each other on the basis of leaves i.e. leaf apex 'A' obtuse and 'B' acute. The 'A' type was fast growing, straight grain and the 'B' type was hardy. Both can be used under agroforestry practices as per site conditions.